Political Conservatives' Affinity for Obedience to Authority Is Loyal, Not Blind. (September 2014) - Frimer, Jeremy A.; Gaucher, Danielle; Schaefer, Nicola K.
Liberals and conservatives disagree about obeying authorities, with conservatives holding the more positive views. We suggest that reactions to conservative authorities, rather than to obedience itself, are responsible for the division. Past findings that conservatives favor obedience uniformly confounded obedience with conservative authorities. We break down obedience to authority into its constituent parts to test the divisiveness of each part. The concepts of obedience (Study 1) and authority (Study 2) recruited inferences of conservative authorities, conflating results of simple, seemingly face valid tests of their divisiveness. These results establish necessary features of a valid test, to which Study 3 conforms. Conservatives have the more positive moral views of obedience only when the authorities are conservative (e.g., commanding officers); liberals do when the authorities are liberal (e.g., environmentalists). The two camps agree about obeying ideologically neutral authorities (e.g., office managers). Obedience itself is not ideologically divisive.